Detection of Candida (Candidozyma) auris by molecular methods and investigation of clinical symptoms of patients in a tertiary hospital in Istanbul - Akkaya, Yuksel; Erdin, Begum Nalca; Aydin, Irfan; Ozel, Ayse Serra; Yilmaz, Ahmet Munir; Cilkiz, Mustafa; Toraman, Zulal Asci (K Faisal Spec Hosp Res Centre, 2025)
BACKGROUND: Candidozyma auris is resistant to many antifungals, spreads rapidly and causes deaths in patient groups with comorbid factors. OBJECTIVES: The aim of this study was to determine the virulence of C. auris, antifungal resistance genes and clinical characteristics of the patients. DESIGN: Retrospective cohort SETTING: Single-center MATERIAL AND METHODS: This study was conducted between August 2022 and December 2023 at & Uuml;mraniye Training and Research Hospital. ITS1-5.8S-ITS2 and ITS1-ITS4 gene regions of the rDNA gene of C. auris isolates identified by VITEK MS v.3.2 were amplified by polymerase chain reaction (PCR) method. These regions were partially sequenced using the Sanger method. The presence of C. aurisspecific CDR1, ERG11, MDR1, ACT1, SAP5, HYR3, ALS5, IFF4, FUR1, PLB3, PGA26 and PGA52 gene regions were determined by PCR. Antifungal susceptibility testing of C. auris was performed with VITEK 2 Compact AST YS08 and SYO. MAIN OUTCOME MEASURES: Variations in C. auris isolates, antifungal resistance and clinical characteristics of patients SAMPLE SIZE: Forty-four isolates from 31 patients RESULTS: According to gene regions, nine different variations were identified in our hospital, with VAR-1 being the most common. Twenty-five (80.6%) of the patients died and isolation of the causative agent was between days 1-30 in 13 (41.9%) patients. Antibiotic use, ICU admission rate, and central venous catheter use in patients were 29 (93.6%), 28 (90.3%), and 21 (67.7%), respectively. Hypertension, diabetes mellitus (DM) and septic shock were found in 14 (45.2%), 13 (41.9%) and 10 (32.3%) patients, respectively. Antifungal resistance rates of the isolates were determined as 97.7% and 84.1% for amphotericin B and fluconazole, respectively. No resistance to micafungin and caspofungin was detected. The survival rate with echinocandin use was 22% (4 patients). CONCLUSION: Identification of gene regions is valuable in determining the pathogenicity of C. auris. . Due to the presence of comorbidi- ties in patients with C. auris, , it is not possible to determine the exact proportion of deaths attributable to C. auris alone. LIMITATIONS: Single center setting; gene regions could not be ex- pressed.
Keywords: Candidemia; polymerase chain reaction; drug resistance